Crystal and Quantum Chemical Exploration of the Potent Monocarbonyl Curcuminoids to Unveil Their Structural and Intriguing Electronic Properties. Issue 12 (26th March 2020) - Ali, Akbar; Din, Zia Ud; Khalid, Muhammad; Tahir, Muhammad Nawaz; Rodrigues‐Filho, Edson; Ali, Bakhat; Asim, Sumreen; Muhammad, Shabbir
Abstract: The two isomeric trifluoromethane and nitro containing monocarbonylcurcuminoids: (1 E, 4 E )‐2‐methyl‐1‐(4‐nitrophenyl)‐5‐(4 (trifluoromethyl)phenyl)penta‐1, 4‐dien‐3‐one (DI‐MNTDO ) and (1 E, 4 E )‐2‐methyl‐5‐(4‐nitrophenyl)‐1‐(4‐(trifluoromethyl)phenyl)penta‐1, 4‐dien‐3‐one (MO‐MNTDO )have been prepared by two consecutive aldol condensation reactions. The chemical structures of the DI‐MNTDO and MO‐MNTDO have been determined using X‐ray crystallographic and spectrometric methods. The single crystal X‐Ray diffraction (SC‐XRD) data reveals that DI‐MNTDO contains two geometrically different molecules in the asymmetric unit, while, MO‐MNTDO contains one molecule in the asymmetric unit. Additionally, molecular geometric parameters, vibrational spectral analysis, as well as electronic properties of the above‐mentioned molecules have been studied utilizing DFT/B3LYP/6‐31G (d, p) approach. The UV‐Vis spectral analysis was performed utilizing the time‐dependent density functional theory (TD‐DFT) with the same level. The natural bond orbitals (NBOs) investigation has been carried out at the B3LYP/6‐311+G(d, p) approach to explain the intramolecular hyper conjugative interactions. A plausible concurrence is acquired between experimental and theoretical findings. The frontier molecular orbitals (FMOs) have been achieved by above‐mentioned level of theory. Subsequently, the global reactivity parameters are calculated using the energies of FMOs. The chemical potential ( μ ) order: [MO‐MNTDO ( μ =‐5.0785 eV )] < [DI‐MNTDO ( μ =‐4.9465 eV )]. The obtained findings in context of stability as well as reactivity indicate that DI‐MNTDO is more stable and less reactive as compared to MO‐MNTDO . Abstract : The two isomeric trifluoromethane and nitro containing monocarbonyl curcuminoids: (1 E, 4 E )‐2‐methyl‐1‐(4‐nitrophenyl)‐5‐(4 (trifluoromethyl)phenyl)penta‐1, 4‐dien‐3‐one (DI‐MNTDO ) and (1 E, 4 E )‐2‐methyl‐5‐(4‐nitrophenyl)‐1‐(4‐(trifluoromethyl)phenyl)penta‐1, 4‐dien‐3‐one (MO‐MNTDO) have been prepared by two consecutive aldol condensation reactions and characterized using SC‐XRD, UV‐VIS, FT‐IR, 1 H NMR and 13 C NMR. Additionally, density functional theory (DFT) calculations was performed to countercheck the experimental findings and to explore the electronic properties.